Pengaruh Rasio Likuiditas, Profitabilitas, dan Solvabilitas terhadap Kinerja Keuangan pada Perusahaan Sektor Transportasi dan Logistik yang Terdaftar Di BEI Periode 2020-2024 - Rahmawati, Eka; Rajagukguk, Peter (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to determine the effect of liquidity, profitability, and solvency ratios on financial performance. The research utilizes a descriptive quantitative approach with panel data regression analysis, using secondary data processed through Eviews 12. The results of the partial test indicate that the liquidity ratio, measured by the Current Ratio (CR), does not significantly affect financial performance, while the profitability ratio, measured by the Net Profit Margin (NPM), has a significant effect on financial performance. The solvency ratio, measured by the Debt to Equity Ratio (DER), does not have a significant effect on financial performance. The results of the simultaneous test show that liquidity, profitability, and solvency ratios, when considered together, have a significant impact on financial performance. The Adjusted R-squared value indicates that 65% of financial performance (ROA) can be explained by liquidity, profitability, and solvency, while the remaining 35% is influenced by other variables outside this research model.